New species of powdery mildews from North Eastern Region of India - NASIM AHMAD*; D.K. AGARWAL, K.C. PUZARI, A.K. SARBHOY (Indian Phytopathology, 2006)
Survey of North Eastern Region of India resulted in collection of a large number of powdery mildews occurring in anamorphic states. Their systematic studies were earned out and as a result ten new species of anamorphic powdery mildews viz., Oidium alysicarpi, O. buddleiae, O. cocculus, O. launeae, O. ocimi-senctum, O. sesame, O. sesbaniae, O. sidae, O. spiraeae and Ovulariopsis mal/oti are described and illustrated.